Computed tomographic enterography adds value to colonoscopy in differentiating Crohn’s disease from intestinal tuberculosis: a potential diagnostic algorithm - Mao, Ren; Liao, Wang-di; He, Yao; Ouyang, Chun-hui; Zhu, Zhen-hua; Yu, Chen; Long, Shun-hua; Chen, Yu-jun; Li, Zi-ping; Wu, Xiao-ping; Lv, Nong-hua; Hu, Pinjin; Chen, Minhu (Endoscopy, 2015)
Background: Crohn’s disease and intestinal tuberculosis (ITB) are chronic granulomatous disorders that are difficult to distinguish. Computed tomographic enterography (CTE) yields striking ﬁndings for Crohn’s disease in the small bowel but its role in differentiating Crohn’s from ITB is undefined. This prospective study aimed to investigate the value of CTE for differential diagnosis between Crohn’s disease and ITB. Patients and methods: 105 consecutive patients (67 Crohn’s, 38 ITB) who underwent CTE and colonoscopy were enrolled. CTE findings and colonoscopic parameters were compared between Crohn’s disease and ITB by blinded reviewers. Based on univariate and multiple logistic regression analyses, a diagnostic algorithm combining colonoscopy and CTE was formulated. and its performance validated on 60 new patients (40 Crohn’s, 20 ITB). Results: On univariate analysis of CTE findings, proximal small-bowel involvement, asymmetrical mural thickening, segmental small-bowel lesions, mural stratification, the comb sign, and mesentery fibrofatty proliferation were significantly more common in Crohn’s disease, whereas mesenteric lymph node change (calcification or central necrosis) and focal ileocecal lesions were more common in ITB. On multivariate analysis, segmental small-bowel involvement (odds ratio [OR] 0.104, 95 % confidence interval [95 %CI] 0.022 – 0.50), and comb sign (OR 0.02, 95 %CI 0.003 – 0.26) were independent predictors of Crohn’s. Combining CTE and colonoscopic findings increased the accuracy of diagnosing either Crohn’s disease or ITB from 66.7 % (70/105) to 95.2 % (100/105) in the development set (P < 0.001). Sensitivity, speciﬁcity, and area under the curve for receiver-operating characteristic (ROC) in the validation dataset were 92.5 %, 80 %, and 0.862 (95 %CI 0.75 – 0.98), respectively. Conclusions: CTE adds unique information to colonoscopy in differential diagnosis between Crohn’s disease and ITB, allowing correct diagnosis in most patients.